Messenger RNAs of Yeast Virus-Like Elements Contain Non-templated 5' Poly(A) Leaders, and Their Expression Is Independent of eIF4E and Pab1 - Vopálenský, Václav; Sýkora, Michal; Mašek, Tomáš; Pospíšek, Martin (Frontiers in microbiology, 2019)
We employed virus-like elements (VLEs) pGKL1,2 from Kluyveromyces lactis as a model to investigate the previously neglected transcriptome of the broader group of yeast cytoplasmic linear dsDNA VLEs. We performed 5' and 3' RACE analyses of all pGKL1,2 mRNAs and found them not 3' polyadenylated and containing frequently uncapped 5' poly(A) leaders that are not complementary to VLE genomic DNA. The degree of 5' capping and/or 5' mRNA polyadenylation is specific to each gene and is controlled by the corresponding promoter region. The expression of pGKL1,2 transcripts is independent of eIF4E and Pab1 and is enhanced in lsm1Δ and pab1Δ strains. We suggest a model of primitive pGKL1,2 gene expression regulation in which the degree of 5' mRNA capping and 5' non-template polyadenylation, together with the presence of negative regulators such as Pab1 and Lsm1, play important roles. Our data also support a hypothesis of a close relationship between yeast linear VLEs and poxviruses.
Keywords: linear cytoplasmic plasmid; Lsm1; poly(A) leader; pGKL; Pab1; eIF4E; poxvirus; virus-like element